Productive Lifecycle of Human Papillomaviruses that Depends Upon Squamous Epithelial Differentiation - Kajitani, Naoko; Satsuka, Ayano; Kawate, Akifumi; Sakai, Hiroyuki (Frontiers in Microbiology, 2012)
The target of human papillomaviruses (HPVs) is stratified epidermis, and the infection causes diseases ranging from benign condylomas to malignant tumors. Infection of HPVs in genital tracts is one of common sexually transmitted infections, and is a major risk factor of cervical cancer. The infection of HPV targets the epithelial cells in the basal layer of epithelium, while progeny virions egress from terminally differentiated cells in the cornified layer, most surface layer of epithelium. In the infected basal cells, viruses maintain their genome DNAs at low copy number, where their productive lifecycle cannot proceed. Progression of viral productive lifecycle requires differentiation of the host cell, indicating there is tight crosstalk between viral replication and host differentiation programs. In this review, we discuss the regulation of the HPV lifecycle controlled by the differentiation program of the host cells.